Do personal values matter? The effects of personal values on hospitality employees' service climate perceptions. (June 2021) - Saito, Hiroaki; Solnet, David; Robinson, Richard; Paulsen, Neil
Abstract: Growing workforce diversity necessitates greater knowledge and understanding of how employee personal attributes alter perceptions of organisational practices. This study investigates the effects of personal values on employee perceptions of service climate in the context of multi-national hotel chains. We employed a sequential explanatory design that yielded unexpected results, indicating little evidence of personal values effects on employee perceptions of service climate. Nonetheless, the study contributes to unfolding the complex mechanisms of service climate antecedents. Situational strength theory and employees' self-suppression of personal values advance understanding of the intersection between personal values, organisational attributes, and employee perceptions of service climate. Future research opportunities are proposed, and theoretical and practical implications are discussed.